Critical Health Communication Methods at the U.S.-Mexico Border: Violence Against Migrant Women and the Role of Health Activism - Hernández, Leandra H.; De Los Santos Upton, Sarah (Frontiers in Communication, 2019)
This essay re/envisions what critical health communication methods look like on the U.S.-Mexico border in reproductive justice contexts. For example, traditional health communication theories and methods have privileged objectivity, generalizability, and the creation of critically important health communication patterns and concepts that have guided the development, deployment, and execution of health communication programs and cultural competence programs. However, in this article, we discuss the utility and application of an intersectional/critical health communication reproductive justice method and envision its praxis in contexts like the U.S.-Mexico border. As two Chicana feminist reproductive justice/health communication scholars, our own research on reproductive feminicides throughout the U.S. and Latin America has necessitated the blending of a variety of theoretical and methodological approaches–border theories, intersectionality, Chicana feminisms, and health communication theories and methods. Thus, this essay traces the blending of these theories and methods and discusses how critical intersectional feminist health communication methods can be utilized in activist ways to resist reproductive and gendered violence at the U.S.-Mexico border.